2014
DOI: 10.1080/13854046.2014.942373
|View full text |Cite
|
Sign up to set email alerts
|

Supervision in Neuropsychological Assessment: A Survey of Training, Practices, and Perspectives of Supervisors

Abstract: Within the psychology supervision literature, most theoretical models and practices pertain to general clinical or counseling psychology. Supervision specific to clinical neuropsychology has garnered little attention. This survey study explores supervision training, practices, and perspectives of neuropsychology supervisors. Practicing neuropsychologists were invited to participate in an online survey via listservs and email lists. Of 451 respondents, 382 provided supervision to students, interns, and/or fello… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Interestingly, respondents were 75% female, suggesting more female trainees responded to this survey compared to the proportion of professional neuropsychologists (Sweet et al, 2015) and supervisors (Shultz et al, 2014) previously surveyed. Additionally, although most internship and postdoctoral trainees secured APA-accredited internships, more Ph.D. than Psy.D.…”
Section: Respondent Characteristicsmentioning
confidence: 83%
See 1 more Smart Citation
“…Interestingly, respondents were 75% female, suggesting more female trainees responded to this survey compared to the proportion of professional neuropsychologists (Sweet et al, 2015) and supervisors (Shultz et al, 2014) previously surveyed. Additionally, although most internship and postdoctoral trainees secured APA-accredited internships, more Ph.D. than Psy.D.…”
Section: Respondent Characteristicsmentioning
confidence: 83%
“…Odland, Ritchie, & Mittenberg, 2012;Shultz, Pedersen, Roper, & Rey-Casserly, 2014). However, no comprehensive surveys of neuropsychology graduate students, interns, and postdoctoral fellows (referred to collectively as trainees hereafter) have yet been conducted.…”
mentioning
confidence: 98%
“…Although many supervision training opportunities appear to exist in training programs, especially within the VA setting (Roper & Caron, 2012), some surveys have found only a small percentage of trainees have actually gained experience in tiered supervision and learning this new supervisory role (Bowers, Ricker, Regan, Malina, & Boake, 2002). This may be changing more recently as Shultz, Pedersen, Roper, and Rey-Casserly (2014) reported that a slight majority or 54% of respondents indicated that they had had experience with tiered supervision. These authors also make the salient point that psychotherapy supervision is more process-focused and distinct from the more didactic approach within their neuropsychology subfield.…”
Section: Perspectives On the Supervisory Rolementioning
confidence: 92%
“…Provision of interventions involves both functional and foundational core competencies according to recent models (Stucky et al 2010). However, training and practice in neuropsychological interventions has been widely neglected, for example, in the United States where less than 48 % of neuropsychologist respondents reported receiving specific training in intervention skills (Shultz et al 2014).This special issue of Neuropsychology Review highlights diverse interventions for two important clinical populations with neurocognitive disorders, namely, people with geriatric and psychiatric conditions. The purpose of this special issue of systematic reviews is to increase scientific knowledge regarding neuropsychological interventions for both clinicians and researchers.…”
mentioning
confidence: 99%
“…Provision of interventions involves both functional and foundational core competencies according to recent models (Stucky et al 2010). However, training and practice in neuropsychological interventions has been widely neglected, for example, in the United States where less than 48 % of neuropsychologist respondents reported receiving specific training in intervention skills (Shultz et al 2014).…”
mentioning
confidence: 99%